Coalition Governments in a Model of Parliamentary Democracy - Siddhartha Bandyopadhyay; Mandar Oak (Fondazione Eni Enrico Mattei (FEEM), 2006)
We analyze the relative importance of party ideology and rents from office in the formation of coalitions in a parliamentary democracy. In equilibrium, the types of coalitions that are formed may be minimal winning, minority or surplus and they may be ideologically `disconnected'. The coalitions that form depend upon the relative importance of rents of office and seat shares of the parties. If rents are high, governments cannot be surplus. With low rents or the formateur close to the median, minority governments occur for a wider ideological dispersion. Further, there is a non-monotonic relationship between connectedness of coalitions and rents.
Keywords: C72; D72; H19; 330; Coalitions; Ideology; Rents; Regierungskoalition; Parlamentarismus; Ideologie; Politische Partei; Rententheorie; Theorie